EFEK DURASI PENGGUNAAN MASKER BEDAH TERHADAP END-TIDAL KARBON DIOKSIDA PADA MAHASISWA FAKULTAS KEDOKTERAN UNIVERSITAS PATTIMURA TAHUN 2021 - PENGEMANAN, VICTORY O; ANGKEJAYA, ONY W; QUE, BERTHA J (Journal Medical Universitas muhammadiyah Makassar, 2024)
Surgical mask is a medical mask used to protect against particles carried through droplets, air, viruses, or bacteria. Prolonged used of masks raises concern because rebreathing masks. This study aims to see whether there is an effect between the duration of wearing a surgical mask on end-tidal carbon dioxide. This research is experimental research. The subjects of this study were 36 people who were taken by simple random sampling technique and divided into the treatment group (wearing a mask for 120 minutes) and the control group (not wearing a mask for 120 minutes). The result of the study at 0 and 30 minutes were analyzed using Mann-Whitney statistical test and at 60, 90, and 120 minutes were analyzed using Independent T-test statistical test. The result at 0 and 30 minutes showed a p value = 0,673 and 0,563 (p>0.05), at 60 minutes showed a p value = 0,867 (p>0.05) in the control group and p value = 0,868 (p>0.05) in the treatment group, at 90 minutes showed a p value = 0,733 (p>0.05) both in the control and treatment group, at 120 minutes showed a p value = 0,956 (p>0.05) both in the control and treatment group, which means that there is no effect between the duration of wearing a surgical mask on end-tidal carbon dioxide in Pattimura University Medical Faculty students in 2021